Uses of humor to teach Mathematics: A didactic proposal - Menezes, Luís (2017)
The Didactics of Mathematics, as a scientific field, seeks to find the most effective teaching methods. In recent years, the inquiry-based mathematics teaching has established as an approach to productive teaching, especially when compared to the transmissive approach. In inquiry-based mathematics teaching, challenging mathematical tasks are an essential element as they serve as a starting point for learning. The humor for instructional purposes has also been affirmed as a possibility to enrich the teaching of Mathematics, performing affective and cognitive functions. In the study presented here, we are developing and applying mathematical tasks with a humorous nature that can fit into inquiry-based mathematics teaching. The first results show good envolvem ent from the students (grades 4 and 5) and the availability of teachers to use this type of tasks.